Ab initio rate constants from hyperspherical quantum scattering: application to H + CH4 --> H2 + CH3. - Kerkeni, B; Clary, D (2004)
A general and practical procedure is described for calculating rate constants for chemical reactions using a minimal number of ab initio calculations and quantum-dynamical computations. The method exploits a smooth interpolating functional developed in the hyperspherical representation. This functional is built from two Morse functions and depends on a relatively small number of parameters with respect to conventional functionals developed to date. Thus only a small number of ab initio points needs to be computed. The method is applied to the H + CH4 --> H2 + CH3 reaction. The quantum scattering calculations are performed treating explicitly the bonds being broken and formed. All the degrees of freedom except the breaking and forming bonds are optimized ab initio and harmonic vibrational frequencies and zero-point energies for them are calculated at the MP2(full) level with a cc-pVTZ basis set. Single point energies are calculated at a higher level of theory with the same basis set, namely CCSD(T, full). We report state-to-state cross sections and thermal rate constants for the title reaction and make comparisons with previous results. The calculated rate constants are in good agreement with experiments.